Respostas

2013-11-28T15:54:48-02:00
Exemplos(2 – y)3 = 23 – 3.(22).y + 3.2.y2 – y3 = 8 – 12y + 6y2 – y3 ou y3– 6y2 + 12y – 8(2w – z)3 = (2w)3 – 3.(2w)2.z + 3.(2w).z2 – z3 = 8w3 – 12w2z + 6wz2 – z3(c – d)3 = c3 – 3c2d + 3cd2 – d3Exemplos:(2x + 2y)3 = (2x)3 + 3.(2x)2.(2y) + 3.(2x).(2y)2 + (2y)3 = 8x3 + 24x2y + 24xy2 + 8y3(w + 3z)3 = w3 + 3.(w2).(3z) + 3.w.(3z)2 + (3z)3 = w3 + 9w2z + 27wz2 + 27z3(m + n)3 = m3 + 3m2n + 3mn2 + n3
a + b)3 = a3 + 3a2b + 3ab2 + b3
(a – b)3 = a3 – 3a2b + 3ab2 – b3
mais quatro exemplo de (a +)³
mais quatro exemplo de (a-)³
mais quatro exemplo de (a-b).³